Survival lessons from a dying Kingfisher: What not to do in the airlines industry in India. Issue 8 (13th July 2015) - Pathak, Atul Arun
Abstract : Purpose: – This article focuses on the lessons that can be learnt from the bankruptcy of Kingfisher airlines (KFA). Design/methodology/approach: – The paper explores the key reasons behind the failure of KFA. It follows the strategic decisions and actions that KFA took over its lifespan. It highlights the key mistakes that it made and how these ultimately contributed to its demise. It recommends the strategies that other companies can follow to avoid the same fate as KFA. Findings: – KFA made many strategic blunders. It frequently and needlessly changed its business model. It unnecessarily spent on providing offerings that customers did not value. It was strategically blinded by the flamboyance of its owner. In addition, it took too long to read the writing on the wall. Even when clear signals were available of the impending crisis it faced, KFA showed limited urgency to resolve the issues. Practical implications: – Companies need to focus on a sharp business model and not try to be everything for everyone. Companies that gain valuable insight of what its customers value and design their business model to satisfy these requirements have higher chance of survival. Social implications: – It concedes that airlines need to balance the interests of multiple stakeholders. These include its owners, managers, employees, customers, regulators and suppliers. KFA was unable to do this consistently and hence could not survive in the dynamic airlines industry in India. Originality/value: – The paper considers the context of the highly dynamic airline industry in India. It is an industry where new competitors are entering, regulatory changes are frequent and industry profitability is low. In such a scenario, companies such as KFA who do not have a consistent and coherent strategy find it difficult to survive. It provides insights into the challenges faced and recommends strategies for the companies to follow so as to improve their chances of long-term survival.